Pagans in late Roman Halikarnassos I - Poulsen, Birte (Proceedings of the Danish Institute at Athens, 1995)
During four campaigns from 1990-1993 the Department of Greek and Roman Studies at Odense University has been excavating part of a Roman building in ancient Halikarnassos. It is situated on Coban Yildizi Street, about 200 m. west of the Maussolleion terrace. Originally, the main interest of the Danish team in the present excavation was to throw light on the town plan of Halikarnassos during the 4th century B.C. and since the area in question had in fact yielded the remains of a strong ashlar wall which seemed to follow the orientation of the late Classical town plan, i.e. 4 degrees north of east, we particularly welcomed the opportunity to excavate in this area. When we started our investigations considerable recent building activity could be observed on the site, and a small building had been erected to the south. Large foundations trenches had been sunk in the western and in the northernmost part of the area, and strong concrete foundations recently laid to the south-east. This work was halted by the Bodrum Museum of Underwater Archaeology, because mosaic floors had turned up. A team from the Museum then undertook excavations from north to south through the central part of the area and cleared part of three rooms decorated with mosaic floors….